Uptake of Bicarbonate Ion in Darkness by Isolated Chloroplast Envelope Membranes and Intact Chloroplasts of Spinach - Poincelot, Raymond P. (1974)
Bicarbonate uptake by isolated chloroplast envelope membranes and intact chloroplasts of spinach (Spinacia oleracea L. var. Viroflay) in darkness exhibited a similar dependency upon temperature, pH, time, and concentrations of isolated or attached envelope membranes. This similarity in uptake properties demonstrates the usefulness of the envelope membranes for the study of chloroplast permeability. Maximal rates for dark HCO(3)(-) uptake by isolated envelope membranes and intact chloroplasts were more than sufficient to account for the maximal rates of photosynthetic CO(2) fixation observed with intact chloroplasts. The active species involved in the uptake process was found to be HCO(3)(-) and not CO(2). The significance of HCO(3)(-) uptake and its relationship to carbonic anhydrase and ribulose diphosphate carboxylase is discussed. Conditions for maximal HCO(3)(-) uptake in darkness by intact chloroplasts were found to be similar to those required for maximal photosynthetic CO(2) fixation, suggesting that HCO(3)(-) uptake by the envelope membrane may regulate photosynthetic CO(2) fixation.